Microsecond-lived quantum states in a carbon-based circuit driven by cavity photons - B. Neukelmance; B. Hue; Q. Schaeverbeke; L. Jarjat; A. Théry; J. Craquelin; W. Legrand; T. Cubaynes; G. Abulizi; J. Becdelievre; M. El Abbassi; A. Larrouy; et al. (Nature Communications)
Abstract Semiconductor quantum dots are an attractive platform for the realisation of quantum processors. To achieve long-range coupling between them, quantum dots have been integrated into microwave cavities. However, it has been shown that their coherence is then reduced compared to their cavity-free implementations. Here, we manipulate the quantum states of a suspended carbon nanotube double quantum dot with ferromagnetic contacts embedded in a microwave cavity. By performing quantum manipulations via the cavity photons, we demonstrate coherence times of the order of 1.3 μs, two orders of magnitude larger than those measured so far in any carbon quantum circuit and one order of magnitude larger than silicon-based quantum dots in comparable environment. This holds promise for carbon as a host material for spin qubits in circuit quantum electrodynamics.